Hypophosphatemia in lung disease. Is there any cause and effect relationship ? - Barmawi Hisyam, Barmawi Hisyam (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Many reports showed that hypophosphatemia is prevalent in patients of lung disease with respiratory failure. Correction for hypophosphatemia may improve respiratory capacity, hence, morbidity and mortality. Serum phosphate levels may reflect intracelluler phosphate pool. A decrease in intracellular phosphate may implicate muscular adenosine tri-phosphate (ATP) and red blood cell 2,3 di-phosphoglycerate (DPG) synthesis. Reduction in respiratory muscle ATP will reduce respiratory since ATP is the the source of energy for muscle contraction. Reduction in red blood cel 2,3 DPG will shift hemoglobin dissociation curve to the left that lead to the disturbance of oxygen extraction by the cells. Hypoxia may be resulted from those processes, therefore, recoils the poor capacity of the respiratory muscle. Underlying primary lung diseases may partly play a role in the genesis of hypophosphatemia. Drugs often used for the disease, such as corticosteroids, xathine identification and treatment of hypophosphatemia in lung disease with or without respiratory failure in order to improve morbidity and mortality of the patients.Keywords : hypophosphatemia - adenosine tri-phosphate - 2,3 di- phosphoglycerate - hypoxia â respiratory- failureÂ